Designing A Socio-Scientific Hypercontent E-Module For Scientific Literacy-Oriented Science Learning In Secondary Level - Meyliana Puji Widyastuti; Erna Retna Safitri; Desi Desi; Noor Dayana Abd Halim (FKIP Universitas Lampung, 2026)
This study aimed to develop a socio-scientific hypercontent e-module for science learning oriented toward scientific literacy at the secondary education level and to determine its validity, practicality, and effectiveness. This research employed a Research and Development (R&D) approach using the ADDIE model, with Tessmer’s formative evaluation during the Development and Evaluation Phases. It consisted of five main phases: Analysis, Design, Development, Implementation, and Evaluation. The development phase consisted of self-evaluation, expert review, one-to-one evaluation, and small group evaluation. The evaluation phase consisted of a field test. The participants were 30 eighth-grade students at SMP Negeri 11 Bayung Lencir. Data were collected through observation sheets, student needs questionnaires, expert validation sheets, student response questionnaires, and scientific literacy tests. The results showed that the developed e-module was categorized as very valid with an average validation score of 95%. The practicality test indicated that the e-module was practical in the one-to-one evaluation (76.6%) and very practical in the small group evaluation (91.8%). The effectiveness evaluation revealed an increase in the average scientific literacy score from 51.2 on the pretest to 87.5 on the posttest, yielding a high N-gain of 0.73. The paired-samples t-test also revealed statistically significant improvements across all four scientific literacy competencies (p < .001), with the greatest improvement observed in the critical interpretation of data and evidence, followed by evaluating scientific investigation designs, using scientific information for decision-making and action, and explaining scientific phenomena. Therefore, the socio-scientific hypercontent e-module was considered valid, practical, and effective for supporting science learning oriented toward scientific literacy at the secondary level. Keywords: socio-scientific issues, hypercontent e-module, scientific literacy, science learning, ADDIE model.